Development Of Sleep Inducer Device with Electromagnetic Field for Therapy - Templer, T.K.; Omar, W.R.W. (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2022)
Sleep affects mental and physical health. Insomnia, obstructive sleep apnea, and restless leg syndrome have been caused by lifestyle, job, and occasionally physiological issues. Sleep deprivation promotes mental and physical disorders. Treatment drugs are addictive and have major adverse effects, while intervention devices are expensive. This project will focus on individual who has difficulty falling asleep. An electromagnetic radiator coil will generate a sleep-friendly environment. The project intends to build a frequency circuit that creates electromagnetic fields as a sleep relaxer, (clock) circuit timer, and sleep-related pulse rate. The 555 Timer, Arduino Uno, a radiator coil, Bluetooth HC-06, LCD 16 x 2 pin, and Proteus Professional 8.12 software for remote testing are included in the product. This project measures pulse oximetry and blood oxygen saturation (SpO2). The project's parameter will be the user's spO2 result, which will be shown with the sleep inducer application that is attached to the phone.